Resistance training for judo: Functional strength training concepts and principles - Henry, T. (Strength and Conditioning Journal, 2011)
Possessing the necessary complex skills and tactical excellence required for success in judo competition requires the athlete be able to move well and efficiently and be absent of postural distortions, faulty movement patterns, and muscular imbalances. Resistance training programs for the judo athlete should include objectives that increase his/her abilities to move efficiently, develop strength, speed, and explosiveness and promote resistance to injury. Incorporating a functional approach to a strength and conditioning program, one that incorporates resistance training techniques that properly train the athlete's situational needs and body function, will further enhance these abilities.